Applications Of Education Media Animation Film, Interactive Software and Comics Toward the Dental Health Behavior of Paud Children in Dental Edu Tour - Subekti, Ani Subekti; Sadimin, Sadimin; Wiradona, Irmanita; Sariyem, Sariyem; Renata, Agnes Lia (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2025)
Education about dental health as early as possible is given to children, especially preschool children, namely PAUD children. PAUD children are a period of learning while playing. Educational activities for PAUD children are provided by the Preventive Promotive Clinic of the Dental Health Department of the Semarang Ministry of Health Poltekkes in the form of dental clinic educational tours. The purpose of this community service is to change the dental health behavior of PAUD children through several dental health education media.The target of community service is 61 Banyumanik Semarang PAUD children, namely Lentera Bunda PAUD, Mutiara PAUD and Pelangi PAUD. Children's age is children aged 3-6 years. This service to PAUD children includes dental health education activities, brushing teeth together and getting to know the dental clinic environment. The education media for the 3 PAUD are divided into 3 types, namely comic media, animated film media and interactive software media. The output of the activity is measured by evaluating the level of children's dental hygiene, knowledge and actions of children and the results of accompanying parents regarding the maintenance of children's dental health.The results of the activity show that all counseling media provide good change/impact for improving the maintenance of children's dental health. Comic education media tends to have a higher impact than animated film media and interactive software. This can be seen from the various aspects studied with the tendency for the greatest increase in the target of comic media intervention. Parental assistance books for maintaining dental and oral health also have a good impact on improving children's behavior. With parental assistance, children will get used to and get used to maintaining dental health.